2012
DOI: 10.1002/ajh.23342
|View full text |Cite
|
Sign up to set email alerts
|

B‐cell receptor configuration and adverse cytogenetics are associated with autoimmune hemolytic anemia in chronic lymphocytic leukemia

Abstract: The development of autoimmune hemolytic anemia (AIHA) in patients with chronic lymphocytic leukemia (CLL) is associated with specific biological features. The occurrence of AIHA was hereby investigated in a retrospective series of 585 CLL patients with available immunoglobulin heavy chain variable (IGHV) gene status. AIHA occurred in 73 patients and was significantly associated with an IGHV unmutated (UM) status (P < 0.0001) and unfavorable [del(17)(p13) and del(11)(q23)] cytogenetic lesions (P < 0.0001). Ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…22, 23 Our study cohort was at increased risk for the development of AIC given the long median duration of CLL, high median number of prior therapies, and relatively high percentage of patients with unmutated IGHV. 24 As an indicator of this risk, 26% of the patients had experienced a least one episode of AIC prior to study enrollment, which is one of the higher reported AIC rates in studies of CLL patients. 2, 25 Despite this, a low rate of treatment emergent AIC was seen, suggesting that ibrutinib reduces the risk of AIC development.…”
Section: Discussionmentioning
confidence: 99%
“…22, 23 Our study cohort was at increased risk for the development of AIC given the long median duration of CLL, high median number of prior therapies, and relatively high percentage of patients with unmutated IGHV. 24 As an indicator of this risk, 26% of the patients had experienced a least one episode of AIC prior to study enrollment, which is one of the higher reported AIC rates in studies of CLL patients. 2, 25 Despite this, a low rate of treatment emergent AIC was seen, suggesting that ibrutinib reduces the risk of AIC development.…”
Section: Discussionmentioning
confidence: 99%
“…IGHV mutational status analysis was performed on total RNA using family‐specific IGHV primers for the leader region, in agreement with ERIC recommendations . Amplicons were analyzed by capillary electrophoresis and sequenced by Ab3130 Genetic Analyzer (Applied Biosystems, Life Technologies Corporation, USA) as previously described . Sequences were aligned to IMGT database and analyzed using IMGT/VQUEST software in order to detect VDJ rearrangement.…”
Section: Methodsmentioning
confidence: 99%
“…In order to detect stereotyped BCR, complete sequences of 34 patients were analyzed as previously described , comparing them with known stereotyped sequences .…”
Section: Methodsmentioning
confidence: 99%
“…Данные о безопасности и эффективности ибрутиниба в качестве монотерапии или в сочетании с глюкокортико-стероидами у больных с ХЛЛ, отягощенным аутоиммун-ным гемолизом, продемонстрированы в ряде междуна-родных исследований [18][19][20][21][22][23][24][25][26].…”
Section: Introductionunclassified